Formula Membangun Integritas Penegak Hukum Melalui Pendekatan Legal Culture dalam Mewujudkan Kejaksaan yang Berwibawa: Formula For Building Law Enforcement Integrity Through A Legal Culture Approach In Realizing An Authoritative Prosecutor's Office - Ahmad Habib Al Fikry (Jurnal Hukum Lex Generalis, 2023)
Law enforcement is an element that also influences the effectiveness of the system and law enforcement. In the process of realizing this legal objective, pragmatically, there needs to be a balance between jusristische logics and juristische ethics. Ethics is an important thing that must always be implemented by the Prosecutor as a law enforcer. A comprehensive formula is needed for the purpose of building integrity as an ethical character that holds value principles. This is in line with the occurrence of several corruption cases which reflect the weakness of the prosecutor's integrity. Legal culture is also an inherent factor in law enforcement, the authors harmonize the two which is then used as an approach in the search for formulas to build integrity. This writing uses a normative juridical research method with a law, case, and conceptual approach. The result of this paper is a formula to build the integrity of the Prosecutor with aspects of divinity and knowledge, management aspects, and structural aspects. All three are used based on a legal culture approach so that they can create an authoritative prosecutor's office and welfare for the people and the state.